Creation of a Field Guide to Camas Prairie Plants with Undergraduates: Project-Based Learning Combined with Epistemological Decolonization - Bowcutt, Frederica (Ethnobiology Letters, 2021)
Remnant camas prairies and associated oak woodlands are the focus of contemporary Indigenous food sovereignty efforts in the Salish Sea (aka Puget Sound) region of western Washington. They are also the focus of research and restoration to conserve at-risk species of animals and plants protected under the United States Endangered Species Act. Currently there is little collaboration between tribes and restoration scientists. These conditions create an opportunity and ethical imperative for developing undergraduate curriculum that highlights the connections between biodiversity conservation and traditional Indigenous ecological knowledge. Patchy mosaic prairie-oak woodland vegetation visibly reflects the imprint of human activity, which includes past burning to foster native food plants including common camas (Camassia quamash) and Oregon white oak (Quercus garryana). Using a floristic research project focused on these cultural landscapes as a case study, this essay illustrates how interdisciplinary inquiry and service learning can enrich college-level plant taxonomy curriculum, while creating rich opportunities for students to link their botanical studies to a historically-grounded understanding of why the conservation challenges exist in the first place. Through this collaborative, multi-year research effort, students contribute to the production of needed resources useful to regional conservation efforts. Affiliated learning communities also consider what it might mean to decolonize botanical knowledge in the context of ecological restoration.